Pembentukan Citra Diri Mahasiswa Fakultas Ilmu Komunikasi Universitas dr. Soetomo Surabaya dalam Instagram (Jurnal Kajian Media, 2018)
This study focuses on the establishment of self-image of students in the University. Soetomo Surabaya in using Instagram social media. This study is a communication research because it examines how the formation of self-image in faculty of communication science students in social media networking in Instagram is needed. The formulation of the problem of this research is how the formation of self-image of students in instagram?. Library review used by researchers is social media instagram as a means of forming self-image, student self-image, Dramaturgi theory. While the method used by researchers is descriptive qualitative. The self-image seen in the students in communication science faculty is about over confidence dominated by female students. This was indicated by several informants selected by the researcher. Based on the interviews, found the data that the formation of self-image through social media Instagram based on aspects that highlighted such as physical, psychological and social aspects.Based on the research conducted by interviews, found the findings that the students of communication science faculty dr soetomo surabaya use instagram in shaping his image, The formation of self-image is always marked by the understanding of instagram users to themselves through the concept of Dramaturgi. Aspects highlighted by the informant vary depending on her understanding. The informant will highlight the part that is understood as an advantage and will cover (save) something that is understood as a weakness Keywords: Instagram, Self image.